Investigations into the Melitaea ornata species complex in the Levant: M. telona and the newly erected species Melitaea klili Benyamini, 2021 (Lepidoptera: Nymphalidae) - Russell, Peter J. C.; Pateman, James E.; Gagarina, Anastasia V.; Lukhtanov, Vladimir A. (Zootaxa, 2023)
Melitaea klili Benyamini, 2021 was recently described from Israel as a species closely related to M. telona Fruhstorfer, 1908, but different in phenology, ecological preferences and with an allopatric distribution. Here, based on comparative examinations of mitochondrial DNA-barcodes, male genitalia and larval behaviour under laboratory conditions, we synonymize M. klili with M. telona. The COI barcodes of M. klili were found to be identical to those of M. telona. Analysis of 658 bp fragment of the mitochondrial gene COI demonstrated that the minimum uncorrected p-distance between M. ornata and M. telona was 1.98%. This value is remarkably less than the 3% threshold traditionally accepted as a species boundary in DNA barcoding studies. The morphological differences between these taxa are minimal. In fact, M. ornata and M. telona represent two phylogenetic lineages, the taxonomic status of which (separate species or subspecies of the same species) is intermediate and debatable.